2018
DOI: 10.1016/j.diabres.2017.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Original paper: Efficacy and safety analysis of insulin degludec/insulin aspart compared with biphasic insulin aspart 30: A phase 3, multicentre, international, open-label, randomised, treat-to-target trial in patients with type 2 diabetes fasting during Ramadan

Abstract: IDegAsp is a suitable therapeutic agent for patients who need insulin for sustained glucose control before, during and after Ramadan fasting, with a significantly lower risk of hypoglycaemia, versus BIAsp 30, an existing premixed insulin analogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…A recent open-label treat-to-target trial randomized 263 subjects from 5 different countries to twice-daily insulin degludecaspart combination (not available in Canada) or biphasic insulin aspart 30. The degludec-aspart combination had significantly lower rates of overall and nocturnal hypoglycemia, with similar A1C efficacy (32). In this trial, the insulin dosage adjustment pre-Ramadan was in tandem with the IDF-DAR recommendations (8).…”
Section: Insulin Management Of Type 2 Diabetes During Ramadanmentioning
confidence: 79%
“…A recent open-label treat-to-target trial randomized 263 subjects from 5 different countries to twice-daily insulin degludecaspart combination (not available in Canada) or biphasic insulin aspart 30. The degludec-aspart combination had significantly lower rates of overall and nocturnal hypoglycemia, with similar A1C efficacy (32). In this trial, the insulin dosage adjustment pre-Ramadan was in tandem with the IDF-DAR recommendations (8).…”
Section: Insulin Management Of Type 2 Diabetes During Ramadanmentioning
confidence: 79%
“…Earlier research also supports the greater risk of hypoglycaemia with SUs compared metformin monotherapy [62]. A number of studies have also shown the lower risk of hypoglycaemia with newer T2 diabetes therapies compared to SUs and their safety in Ramadan fasting [58,59,[63][64][65][66][67][68][69][70][71].…”
Section: Hypoglycaemiamentioning
confidence: 86%
“…Second-generation insulins may offer less glycaemic variability and hypoglycaemia and hence have a potential for use in Ramadan. The combination of insulin degludec/degludec and aspart insulin (IDegAsp) has been shown to be a safe and efficacious therapy during Ramadan [ 64 , 140 ]. In a recent real-world observational study, patients with T2 diabetes fasting in Ramadan who were taking insulin glargine 300 units/ml showed a low risk of severe/symptomatic hypoglycaemia and improved control [ 141 ].…”
Section: Managementmentioning
confidence: 99%
“…In a randomised treat-to-target trial, IDegAsp BID provided sustained glucose control before, during and after Ramadan fasting in patients with T2D previously treated with basal or premixed insulin ± OADs, with a significantly lower risk of hypoglycaemia than BIAsp 30 BID [62]. Doses of IDegAsp BID and BIAsp 30 BID were reduced by 30%-50% on the first day of Ramadan and readjusted to pre-Ramadan levels at the end of Ramadan.…”
Section: Patients On a Very-low-calorie Reduced-carbohydrate Or Erramentioning
confidence: 99%